Virtual Private Network Analysis Point To Point Tunneling Protocol - Adiman Adiman; Indra Kanedi; Reno Supardi (Jurnal Media Computer Science, 2022)
This research aims to conduct a network analysis of the Virtual Private Network Point To Point Tunneling Protocol at the UPTD of the Bengkulu Province Cooperatives and SMEs Training Center. to carry out activities that occur on the wifi network at the UPTD Cooperatives and UKM Training Center Bengkulu Province and also as one of the requirements for obtaining a bachelor's degree in the Department of Informatics, Dehasen Bengkulu University. The research method used is the Network Development Life Cycle (NDLC) method which aims at the process of making and designing a Virtual Private Network Point To Point Tunneling Protocol using a mikrotik RB951Ui-2HnD. The process of making and designing is how to connect the proxy with a computer then by making a remote access remote from the mikrotik location using the Winbox application. Mikrotik can configure a network that is needed on the UPTD network of the Bengkulu Province Cooperatives and SMEs Education and Training Center by applying remote access remotely, the remote results and security when logging in to the Mikrotik connection can be done by applying the network login and password display so that it is secure when connecting to the mikrotik. and can make it easier for us to operate the mikrotik network remotely and safely.